PERANCANGAN VOICE OVER INTERNET PROTOCOL (VoIP) MENGGUNAKAN VIRTUAL PRIVATE NETWORK (VPN) PADA PT CARE TECHNOLOGIES - Rusdiansyah Rusdiansyah; Herlawati Herlawati; Eka Puspita Sari (Jurnal Techno Nusa Mandiri, 2013)
Current technological developments to make a change from several sides. As in telecommunications are now developed with incoming. One of them is VoIP. VoIP is a technology capable of passing voice in packet form. With this VoIP technology, one can make telephone communication via the internet. To use this VoIP one can use the handphones are connected tolapop or PC. However, the use of VoIP has a disadvantage that can be done tapping at the time the conversation is being conducted. VPN (Virtual Private Network) is a way of creating a private network are using a public network / Internet. With a VPN network, a user as if connected by point to point that they are not. Consists of VPN-management protocols that can perform encryption and tunneling as PPTP (Point to Point Protocol), L2TP (Layer 2 Tunneling Protocol) and IPSec(Internet Protocol Security). With the capabilities of the VPN is expected that the wiretapping of conversations being conducted by the user can be prevented.